ISU COVID-19 SEBAGAI IDE BESAR DALAM STRATEGI KREATIF IKLAN, SEBAGAI KEPENTINGAN PENJUALAN ATAUKAH PENCITRAAN? - Jiwa Utama; Rahmiati Aulia (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2021)
Using something currently popular among the intended target audience is a natural thing to be appointed as a big idea in an advertisement. However, what if the COVID-19 (coronavirus) pandemic that is hitting many countries worldwide, including Indonesia, causes many sufferers and casualties? The issue wants to show the care of the brand towards the audience as consumers, or is it just for the sake of selling? This study uses purposive sampling from identifying problems, namely analyzing several product advertisements that used the covid-19 pandemic issue with a qualitative method. Where advertisements will be studied using content analysis to find out how to approach communication and visuals, then will be discussed with a creative strategy theory approach in advertising. This study aims to find out the pattern of creative strategies used and to answer what interests are contained in the pattern of creative strategies based on the formulation of the problems that have been mentioned. The study results do not show any sales interest solely in categories that display the coronavirus based on an assessment of advertising messages. However, one of the findings of communication that says can use other brand products where the advertisement of a product usually only prioritizes the interests of the product so that the audience believes in the product and will only use the product, which of course will not recommend competing products.